ZAKAT HASIL PERTANIAN KONTEMPORER - Zainuddin, Cholidi (Universitas Islam Negeri Raden Fatah Palembang, 2013)
Abstract: Every moslem pays zakat (obligatory alms) as a realization a of five pillars of Islam. There are two kinds of zakat, Poverty principle and Fitrah zakat. Zakat of agricultural product is a part of Poverty Zakat. Based on tradition of the Prophet which was expressed by Tabrani and Hakim from Abu Musa al-Asy’ari and Muaz bin Jabal, there were four kinds of agricultural product which must be paid, namely syair, wheat, wine, and date. There are some other agricultural products besides the four that must be researched. There are two opinions. The first, there is no obligation to pay zakat. It was based on the tradition of the Prophet above. The second, there is an obligation to pay zakat. It was based on the Qiyas. Hanafi and Ibrahim Hosen said that supporting life was the illat of the obligation of zakat.ملخص: على المسـلم أن يؤتي الزكاة كإحدى الواجبات الخمسة الموجودة فى أركان الإسـلام. الزكاة نوعان: زكاة الأموال وزكاة الفطر، وزكاة حاصلات الزراعة من زكاة الأموال. روى فى الحديث للإمام الطبرنى والحاكم عن أبى موسى الأشـعرى ومعاذ بن جبل أن هناك أربعة أنواع من حاصلات الزراعة التى يجب إخراج زكاتها وهى الشعـير والقـمح والعـنب والتـمر. وهناك الحاصلات الأخرى غـير ما ذكره الحديث الذى لا يزال يحتاج إلى البحث فى وجوب إخراج الزكاة عنها. وفـيها رأيان: (1) لا يجب إخراج الزكاة عنها لحديث مذكور و (2) يجب إخراج الزكاة عنها. Kata Kunci: zakat, hasil pertanian, kontemporer